Sinähän et kyllä minun silmille tuolla tavalla hypi: Neljän liikunnanopettajan erilaiset tavat suhtautua häiriökäyttäytymiseen - Saukkoriipi, Samu (2018)
Saukkoriipi, S. 2017. You stop that at once: The different ways in which four physical education teachers deal with misbehavior. Faculty of Sport Sciences. University of Jyväskylä. Master`s thesis in Sports Pedagogy, 97 pp. 2 appendices.